Bias-induced threshold voltages shifts in thin-film organic transistors - Gomes, Henrique L. (2015)
An investigation into the stability of metal-insulator-semiconductor (MIS) transistors based on alpha-sexithiophene is reported. In particular, the kinetics of the threshold voltage shift upon application of a gate bias has been determined. The kinetics follow stretched-hyperbola-type behavior, in agreement with the formalism developed to explain metastability in amorphous-silicon thin-film transistors. Using this model, quantification of device stability is possible. Temperature-dependent measurements show that there are two processes involved in the threshold voltage shift, one occurring at Tapproximate to220 K and the other at Tapproximate to300 K. The latter process is found to be sample dependent. This suggests a relation between device stability and processing parameters. (C) 2004 American Institute of Physics.